2020
DOI: 10.1111/tbed.13716
|View full text |Cite
|
Sign up to set email alerts
|

Candidatus Mycoplasma haemoalbiventris’, a novel hemoplasma species in white‐eared opossums ( Didelphis albiventris ) from Brazil

Abstract: Opossums of the genus Didelphis are considered synanthropic animals due to their close contact with human beings. Previously, two species of hemotropic mycoplasmas (hemoplasmas) have been detected in opossums: 'Candidatus Mycoplasma haemodidelphidis' in the North American opossum (Didelphis virginiana) and a potentially novel hemotropic Mycoplasma sp. in the white-eared opossums (Didelphis albiventris) from Brazil. Accordingly, the aims of this study were as follows: (a) to determine the prevalence of hemotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
(48 reference statements)
2
20
1
Order By: Relevance
“…This haemoplasma has been recently proposed to be a novel species, named Ca. M. haemoalbiventris, according to sequence analysis of 16S and 23S rRNA gene amplicons (Pontarolo et al, 2020). In another study, none out of 30 specimens of four species, including some white-eared opossums, were infected by haemoplasmas (de Sousa et al, 2017).…”
Section: Marsupialsmentioning
confidence: 98%
“…This haemoplasma has been recently proposed to be a novel species, named Ca. M. haemoalbiventris, according to sequence analysis of 16S and 23S rRNA gene amplicons (Pontarolo et al, 2020). In another study, none out of 30 specimens of four species, including some white-eared opossums, were infected by haemoplasmas (de Sousa et al, 2017).…”
Section: Marsupialsmentioning
confidence: 98%
“…The gapdh gene was consistently amplified in all ring-tailed coati (Barker et al, 2011;Pontarolo et al, 2021;Valente et al, 2020;Vieira et al, 2021). On this pattern, the 23S rRNA sequences amplified in the present study showed only 94.3%-94.1% identity to 'Ca.…”
Section: Resultsmentioning
confidence: 49%
“…M. haemoalbiventris', while all the animals from Curitiba City tested negative. Previous studies have found higher hemoplasma prevalence rates (ranging from 32.5-87.5%) in white-eared opossums from different geographic regions and biomes (Atlantic Forest and Cerrado) of Brazil (Massini et al, 2019;Gonçalves et al, 2020;Pontarolo et al, 2021). Although Curitiba City is also located in the Atlantic rainforest biome, we hypothesize that its altitude (940 m a.s.l.)…”
mentioning
confidence: 79%
“…Hemotropic mycoplasmas (hemoplasmas) are Gram-negative bacteria that attach to the surface of red blood cells from mammals and may cause hemolytic anemia. Two hemotropic Mycoplasma species have been described in Didelphis, namely 'Candidatus Mycoplasma haemodidelphis' (Messick et al, 2002) and 'Candidatus Mycoplasma haemoalbiventris' (Pontarolo et al, 2021). Due to the proximity of human dwellings and human-animal interactions, monitoring ticks and the health status of opossums is a public health concern.…”
mentioning
confidence: 99%
See 1 more Smart Citation